TH17 cells promote microbial killing and innate immune sensing of DNA via interleukin 26 - Meller, Stephan; Di Domizio, Jeremy; Voo, Kui S; Friedrich, Heike C; Chamilos, Georgios; Ganguly, Dipyaman; Conrad, Curdin; Gregorio, Josh; Le Roy, Didier; Roger, Thierry; Ladbury, John E; Homey, Bernhard; et al. (Nature immunology, 2015)
T H 17 cells have important roles at mucosal surfaces in both health and disease. Gilliet and colleagues show that IL-26 is preferentially produced by human T H 17 cells and that this cytokine has both alarmin and direct antimicrobial functions. Interleukin 17–producing helper T cells (T H 17 cells) have a major role in protection against infections and in mediating autoimmune diseases, yet the mechanisms involved are incompletely understood. We found that interleukin 26 (IL-26), a human T H 17 cell–derived cytokine, is a cationic amphipathic protein that kills extracellular bacteria via membrane-pore formation. Furthermore, T H 17 cell–derived IL-26 formed complexes with bacterial DNA and self-DNA released by dying bacteria and host cells. The resulting IL-26–DNA complexes triggered the production of type I interferon by plasmacytoid dendritic cells via activation of Toll-like receptor 9, but independently of the IL-26 receptor. These findings provide insights into the potent antimicrobial and proinflammatory function of T H 17 cells by showing that IL-26 is a natural human antimicrobial that promotes immune sensing of bacterial and host cell death.